An integrated care programme in London: qualitative evaluation. Issue 4 (15th October 2018) - Round, Thomas; Ashworth, Mark; Crilly, Tessa; Ferlie, Ewan; Wolfe, Charles
Abstract : Purpose: A well-funded, four-year integrated care programme was implemented in south London. The programme attempted to integrate care across primary, acute, community, mental health and social care. The purpose of this paper is to reduce hospital admissions and nursing home placements. Programme evaluation aimed to identify what worked well and what did not; lessons learnt; the value of integrated care investment. Design/methodology/approach: Qualitative data were obtained from documentary analysis, stakeholder interviews, focus groups and observational data from programme meetings. Framework analysis was applied to stakeholder interview and focus group data in order to generate themes. Findings: The integrated care project had not delivered expected radical reductions in hospital or nursing home utilisation. In response, the scheme was reformulated to focus on feasible service integration. Other benefits emerged, particularly system transformation. Nine themes emerged: shared vision/case for change; interventions; leadership; relationships; organisational structures and governance; citizens and patients; evaluation and monitoring; macro level. Each theme was interpreted in terms of "successes", "challenges" and "lessons learnt". Research limitations/implications: Evaluation was hampered by lack of a clear evaluation strategy from programme inception to conclusion, and of the evidence required to corroborate claims of benefit. Practical implications: Key lessons learnt included: importance of strong clinical leadership, shared ownership and inbuilt evaluation. Originality/value: Primary care was a key player in the integrated care programme. Initial resistance delayed implementation and related to concerns about vertical integration and scepticism about unrealistic goals. A focus on clinical care and shared ownership contributed to eventual system transformation.